2016
DOI: 10.3389/fnbeh.2016.00040
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of Three-Dimensional Space in Fish

Abstract: In mammals, the so-called “seat of the cognitive map” is located in place cells within the hippocampus. Recent work suggests that the shape of place cell fields might be defined by the animals’ natural movement; in rats the fields appear to be laterally compressed (meaning that the spatial map of the animal is more highly resolved in the horizontal dimensions than in the vertical), whereas the place cell fields of bats are statistically spherical (which should result in a spatial map that is equally resolved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Given the anisotropic neural coding observed in these spaces, the increased energetic cost of moving vertically and the increased computational demands of planning trajectories, the aim of the current experiment was to investigate how rats navigate three-dimensional volumetric environments. Because of the evolutionary and kinaesthetic differences between ecologically volumetric animals such as fish (Burt de Perera et al 2016 ) and bats (Yartsev and Ulanovsky 2013 ) when compared to humans, we used rats as a closer biological and electrophysiological model. Despite their essentially surface-bound nature, rats exhibit many three-dimensional behaviours similar to those of humans.…”
Section: Introductionmentioning
confidence: 99%
“…Given the anisotropic neural coding observed in these spaces, the increased energetic cost of moving vertically and the increased computational demands of planning trajectories, the aim of the current experiment was to investigate how rats navigate three-dimensional volumetric environments. Because of the evolutionary and kinaesthetic differences between ecologically volumetric animals such as fish (Burt de Perera et al 2016 ) and bats (Yartsev and Ulanovsky 2013 ) when compared to humans, we used rats as a closer biological and electrophysiological model. Despite their essentially surface-bound nature, rats exhibit many three-dimensional behaviours similar to those of humans.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, place cells and head direction cells found in flying bats were observed to be sensitive to all 3 axes ( Yartsev and Ulanovsky 2013 ; Finkelstein et al 2014 ). Behavioral experiments with fish also indicated a volumetric 3D representation of space ( Burt de Perera et al 2016 ). However, as suggested by Jeffery et al (2015) , extending spatial encoding from 2D to 3D space comes with complications such as the noncommutative property of 3D rotation, and a fully volumetric representation of 3D space might be costly and unnecessary for certain environments and species.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this seems not to be the case: Yartsev and Ulanovsky ( 2013 ) showed that place cells in flying bats seem to encode space similar along the horizontal and vertical dimensions. A study on pelagic fish reported that these fish possess isotropic representations of the environment (Burt de Perera et al 2016 ). These findings suggest that isotropy versus anisotropy of 3D spatial representations depends on the investigated species.…”
Section: Introductionmentioning
confidence: 99%